A comparative 3d finite element computational study of stress distribution and stress transfer in small-diameter conical dental implants - Kalay O.C.; Karaman H.; Karpat F.; Doğan O.; Yüce, Celalettin (Strojarski Facultet, 2021)
The implant design is one of the main factors in implant stability because it affects the contact area between the bone and the implant surface and the stress-strain distribution at the bone-implant interface. In this study, the effect of different groove geometries on stress-strain distributions in small-diameter conical implants is investigated using the finite element method (FEM). Four different thread models (rectangular, buttressed, reverse buttressed, and symmetrical profile) are created by changing the groove geometry on the one-piece implants, and the obtained results are compared. The stress shielding effect is investigated through the dimensionless numbers that characterize the load-sharing between the bone-implant. It is determined that the lowest stress distribution is observed with rectangular profiled groove geometry. Besides, it is obtained that the buttressed groove geometry minimizes the stress effects transmitted to the periphery of the implant. The symmetrical profiles had better performance than rectangular profiles in stress transfer.
Keywords: Finite element method; Groove geometry; Implant; Implant design